The presentation of the user in reports of information behaviour research - Lynne (E.F.) McKechnie; Jennifer L. Pecoskie; Christopher M. Dixon (Information Research: An International Electronic Journal)
Introduction. This study examined how human information behaviour researchers present research study participants through the following research questions: How do human information behaviour researchers describe participants in reports of empirical research?; and, What strategies do human information behaviour researchers use in their presentation of participants? Method. and Analysis. A content analysis was conducted of 96 research reports published in the 1996-2004 ISIC proceedings. Articles were coded for data collection and data analysis methods, the use of theory, and parts of the article (title, abstract, literature search, method, findings, discussion/conclusion) where participants were included. Also noted were terms used to label research participants, data collection practises and strategies used by authors to present users. Results. Authors use a variety of terms and data collection practices that construct the user/participant as both peripheral and central to research. Conclusion. Researchers must bring greater consciousness to the conduct and reporting of their research. Improvements are needed in doctoral training, research methods texts and publishers' instructions to authors.